DINAMIKA PENGELOLAAN BPHTB SETELAH DIALIHKAN MENJADI PAJAK DAERAH (STUDI KASUS PADA KOTA KEDIRI DI PROVINSI JAWA TIMUR) - Tiara Juniar Soewardi; Candra Fajri Ananda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study conducted to know about the dynamics of BPHTB tax diverted into regional tax in Kediri city, in the light of BPHTB diversion into regional tax. The dynamics meant here is the implementation of the management and BPHTB collection in Kediri City since diverted into local taxes, both benefits and barriers that occurred. This study used qualitative method, with descriptive approach. The source of data obtained from in-depth interview, documentation, observation, and secondary data that complete this study. Result of this study shows that kediri city is prepared enough to face the diversion of BPHTB to regional tax, this can be seen from the institutional side (the act, organization, and practical procedure), and infrastructures and human resources that well enough, even there are still some of the aspects that needs to be improved. Motivation of kediri government to fix the regulation suitable with the its regional condition become a supporting factor for BPHTB diversion in Kediri city, and proved from the elimination of validation, in accordance with letter from BPN, that is SE BPN No 5/SE/IV/2013. And the lack of quality from human resources, especially in the field of appraisal, field check, and the management of tax affairs become the inhibitors of the speed and practice of BPHTB collection. Cooperation between regional government has been maintained well, and this can be seen from the coordination that has been done with related party each year, and resulted in the quick response on the emerging problem. Those factors become the consideration of the government to judge the correct policy to fix the BPHTB collection management after being diverted into regional tax. Further studies needed in the area of the suitability from BPHTB tax with PPh-PHTB to avoid tax fraud. Regional government also have to decide a farming policy which is suitable for the condition of the surrounding area that it governs. Keywords : BPHTB, local/regional tax, local taxing power, regional development funding